HUBUNGAN ANTARA KEMAMPUAN MEMORI DAN MOTIVASI BELAJAR BIOLOGI DENGAN HASIL BELAJARBIOLOGI RANAH KOGNITIF SISWA SMA NEGERI 2 MADIUN TAHUN PELAJARAN 2011/2012 - Habsari, Afrisa Mustika; Karyanto, Puguh; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The aims of the research were to find out the correlation between: 1) memory ability with cognitive learning achievement of biology of student of SMA Negeri 2 Madiun in academic year of 2011/2012, 2) learning motivation of biology with cognitive learning achievement of biology of student of SMA Negeri 2 Madiun in academic year of 2011/2012,3) memory ability and learning motivation of biology with cognitive learning achievement of student of SMA Negeri 2 Madiun in academic year of 2011/2012. This is a correlational research. The population taken were all of the students of SMA Negeri 2 Madiun in academic year of 2011/2012. The sample was taken among 676 samples of student using stratified random sampling technique. Documentation technique was used to uncover student?s cognitive learning achievement and memory ability was measured by using testtechnique. While learning motivation of biology was measured by using questionnaire technique. The obtained data was analysed using linier regression analysis in SPSS 16. The results showed that (1) there was a positive correlation between memory ability with cognitive learning achievement of biology ofstudentof SMA Negeri 2 Madiun in academic year of 2011/2012, 2) there was a positive correlation between learning motivation of biology with cognitive learning achievement of biology ofstudentof SMA Negeri 2 Madiun in academic year of 2011/2012, 3) there was a positive correlation between memory ability and learning motivation of biology with cognitive learning achievement of biology of student of SMA Negeri 2 Madiun in academic year of 2011/2012. Each of independent variable, that is memory ability and learning motivation of biology has contribution to dependent variable, that is cognitive learning achievement of biology. Keywords :Memory ability, learning motivation,cognitive learning achievement in biology, linier regression analysis